Development of Free-floating High Voltage Four-terminal Bidirectional Thyristor Device - TANG Ge; YAN Ji; CAO Guohong; ZHU Weiwei (Kongzhi Yu Xinxi Jishu)
Conventional thyristors in antiparallel structure have been widely used in high voltage soft starters, electrical drives and static var compensators (SVC), but they does not apply in the areas where volume and weight are strictly required. According to thyristors in antiparallel application requirements and based on TCAD semiconductor chip design simulation platform, the bidirectional thyristor chip structure and components assembly structure have been simulated, anti-interference ability of the chip has been improved by the improvement of carrier concentration in the short-base, optimization of short-circuit point and design of PNP horizontal separation structure, and free-floating high voltage four-terminal bidirectional thyristor (BCT) has been successfully developed, which simplifies antiparallel component structure and reduces the size, weight and cost of the assembly component.